2020
DOI: 10.1098/rsif.2020.0094
|View full text |Cite
|
Sign up to set email alerts
|

Transient indicators of tipping points in infectious diseases

Abstract: The majority of known early warning indicators of critical transitions rely on asymptotic resilience and critical slowing down. In continuous systems, critical slowing down is mathematically described by a decrease in magnitude of the dominant eigenvalue of the Jacobian matrix on the approach to a critical transition. Here, we show that measures of transient dynamics, specifically, reactivity and the maximum of the amplification envelope, also change systematically as a bifurcation is approached in an importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 67 publications
0
24
0
Order By: Relevance
“…processes 30 . However, the early warning signal is apparent in the variable x for the prevalence of pro-vaccine opinion, and the DL algorithm outperforms both lag-1 AC and variance in this respect.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…processes 30 . However, the early warning signal is apparent in the variable x for the prevalence of pro-vaccine opinion, and the DL algorithm outperforms both lag-1 AC and variance in this respect.…”
Section: Resultsmentioning
confidence: 99%
“…For the SEIRx coupled behaviour-disease model, all of the classifiers are little better than random in the model variable for the number of infectious persons ( I , Figure 2e). This occurs due to non-normality of the system associated with differing timescales for demographic and epidemiological processes 30 . However, the early warning signal is apparent in the variable x for the prevalence of pro-vaccine opinion, and the DL algorithm outperforms both lag-1 AC and variance in this respect.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The threshold R t = 1 corresponds to a (dynamic) transcritical bifurcation, which is a type of bifurcation that is preceded by critical slowing down (Kéfi et al, 2014;Kuehn, 2011). Early warning indicators based on critical slowing down have been studied extensively and led to a promising research line that aims to utilize them as a tool to forecast the (re)emergence as well as the elimination of infectious diseases (e.g., Brett et al, 2017;Brett et al, 2018;Dessavre et al, 2019;Dibble et al, 2016;Drake et al, 2019;Harris et al, 2020;Miller et al, 2017;O'Dea et al, 2018;O'Regan & Burton, 2018;O'Regan & Drake, 2013;O'Regan et al, 2020;Southall et al, 2020). Accordingly, some researchers have suggested that they could have been used to anticipate the second wave of COVID-19 (Liu et al, 2021;O'Brien & Clements, 2021;Proverbio et al, 2021).…”
Section: Introductionmentioning
confidence: 99%